2023
DOI: 10.1177/23247096231206333
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic Diabetic Keto Acidosis in a Type 1 Diabetic Patient After Glucose Like Peptide-1 Administration: A Case Presentation

Cameron Widhalm,
Victor Pulido

Abstract: Type 1 diabetes mellitus (DM) occurs when insulin-producing beta cells are destroyed. Destruction of these cells and subsequent loss of insulin signaling can cause diabetic keto acidosis (DKA). This case describes a type 1 DM patient who presented to the emergency department (ED) with nausea and vomiting after glucose like peptide-1 (GLP-1) agonist administration. The patient was noted to have elevated anion gap and elevated beta-hydroxybutyrate with euglycemic blood glucose levels. The patient was confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a case report of ketoacidosis resulting from an injection of Wegovy 1.7 mg for the treatment of type 1 diabetes mellitus (T1DM), the effects of appetite suppression and inhibition of gluconeogenesis and glycogenolysis produced by GLP-1 RAs contributed to the reduction of the patient’s insulin push and induced the development of diabetic keto acidosis. Moreover, this could become more prevalent with the widespread use of GLP-1 RAs ( Widhalm and Pulido, 2023 ). A meta-analysis of GLP-1 RAs as adjuvant therapy in patients with T1DM also observed that liraglutide was associated with higher odds of ketosis (OR 1.8; 95% CI, 1.1–2.8) ( Park et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a case report of ketoacidosis resulting from an injection of Wegovy 1.7 mg for the treatment of type 1 diabetes mellitus (T1DM), the effects of appetite suppression and inhibition of gluconeogenesis and glycogenolysis produced by GLP-1 RAs contributed to the reduction of the patient’s insulin push and induced the development of diabetic keto acidosis. Moreover, this could become more prevalent with the widespread use of GLP-1 RAs ( Widhalm and Pulido, 2023 ). A meta-analysis of GLP-1 RAs as adjuvant therapy in patients with T1DM also observed that liraglutide was associated with higher odds of ketosis (OR 1.8; 95% CI, 1.1–2.8) ( Park et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%